KARDIOCHIRURGIA DOROSŁYCHLong-term outcomes of redo coronary-artery bypass grafting - Zwoliński, Radosław; Jaszewski, Ryszard; Pawłowski, Witold; Walczak, Andrzej; Bobiarski, Jerzy; Ostrowski, Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Surgical revascularization, though a well-accepted method of treatment for coronary artery disease, does not prevent complications resulting from the progression of disease. Therefore, some patients with recurrent angina require invasive reinterventions including coronary artery bypass grafting (CABG). The purpose of this study was to evaluate early and late results of reoperative coronary artery bypass grafting in patients operated in our institution in the years 2003-2008. Material and methods : We retrospectively analyzed morbidity, mortality, and functional status of 26 patients (23 men and 3 women) with follow-up time after the redo procedure ranging from 2 months to 29 years. Results : There was only one in-hospital death (3.8%). Two patients died within 30 days of the surgery (7.7%), one of them being dialyzed due to acute renal failure. No remote deaths were recorded. Intra-aortic balloon pump (IABP) counter-pulsation was used in 2 patients (7.7%). No sternal infections or neurological incidents were reported. All patients were asymptomatic or a significant reduction in angina symptoms was observed in late follow-up. Conclusions : Redo CABG is a safe procedure associated with a relatively low morbidity and low early mortality rate.